The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/(sici)1096-9861(19970721)384:1<26::aid-cne2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Development of primary visual projections occurs entirely postnatally in the fat-tailed dunnart, a marsupial mouse,Sminthopsis crassicaudata

Abstract: We have examined the development of retinal projections in a diminutive polyprotodont marsupial, the fat-tailed dunnart, Sminthopsis crassicaudata. Here, we document the most immature mammalian visual system at birth described to date. At postnatal day (P) 0, the retinal ganglion cell layer has yet to form, and axons have not entered the optic stalk. By P4, the retinal ganglion cell layer could be distinguished at the posterior pole, and the front of growing axons extended one-third the length of the optic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…No additional animals were killed. Data were obtained from Tables 1^5 of Robinson and Dreher (1990), Table 2 from Finlay and Darlington (1995), Tables 1^3 of Ashwell et al (1996), data reported in Dunlop et al (1997), Table 1 of Darlington et al (1999), as well as from the general literature where noted. Data for the cortical events in this study refer to posterior (presumptive visual) cortex.…”
Section: Data Used To Construct the Comparative Mammalian Modelmentioning
confidence: 99%
“…No additional animals were killed. Data were obtained from Tables 1^5 of Robinson and Dreher (1990), Table 2 from Finlay and Darlington (1995), Tables 1^3 of Ashwell et al (1996), data reported in Dunlop et al (1997), Table 1 of Darlington et al (1999), as well as from the general literature where noted. Data for the cortical events in this study refer to posterior (presumptive visual) cortex.…”
Section: Data Used To Construct the Comparative Mammalian Modelmentioning
confidence: 99%
“…In grey squirrels the AOS nuclei are already innervated at birth (Cusick and Kaas, 1982), although these retinal projections undergo redistribution during postnatal development. Studies in the marsupial fat-tailed dunnart (Dunlop et al, 1997) have shown that the development of visual pathways in general and of accessory optic projections in particular, occurs entirely postnatally in this species: retinal projections don't reach the accessory optic nuclei until P15. This makes the dunnart a suitable species for studies on the development of the visual system.…”
Section: Ontogenymentioning
confidence: 99%
“…Their lack of a pouch and their fetal‐like nature at birth circumvents the need for in utero experimental procedures that would be required on more conventional mammalian model systems such as mice, rats, rabbits, ferrets, or cats. Thus, their immaturity at birth and their protracted period of postnatal development make marsupials, like Monodelphis , excellent models for the study of visual system development and plasticity 17–22…”
Section: Monodelphis Domestica: a Novel In Vivo Model System To Invesmentioning
confidence: 99%